REVISIÓN TAXONÓMICA DEL GÉNERO NOTOCYMATODERA SCHENKLING 1907 (COLEOPTERA: CLERIDAE) - Solervicens A., Jaime (Acta Entomológica Chilena, 2022)
A revisión of the genus Notocymatodera Schenkling, 1907 is made. Cymatodera modesta Spinola, 1849 (nec Spinola, 1844) correspond to a missidentification and is synonymized with Notocym atodera dimidiata (Germain, 1855). A redescription of N. dimidiata (Germain, 1855), type species of the genus, is made and its geographic distribution is determined. A new species, N. variabilis, is described.